A highly flexible semi-tubular carbon film for stable lithium metal anodes in high-performance batteries. (August 2017) - Huang, Siya; Tang, Lu; Najafabadi, Hasan Salehi; Chen, Shuo; Ren, Zhifeng
Abstract: As the lightest and most electropositive material, lithium metal is regarded as the ultimate anode material for next-generation high-energy batteries. However, uncontrolled dendritic lithium growth as well as low Coulombic efficiency hinders its widespread application in secondary batteries. Interfacial modification of anodes with protective layers has been proved to be an effective way to inhibit the growth of ramified lithium. Here we report on a freestanding, highly flexible nanostructured carbon film, which is ready to be transferred onto electrodes with great ease. We show that such mechanically robust carbon films can effectively suppress the growth of Li dendrites upon cycling at practical current densities (0.25–1.0 mA cm −2 ) with significantly improved Coulombic efficiency up to 99.5% for over hundreds of cycles and thousands of operation hours. Notably, this semi-tubular carbon film demonstrated instant, reliable protection to electrodes in not only reactive electrolytes but also ambient environment with high humidity, offering a practically feasible route toward the dendrite-free lithium metal batteries. Graphical abstract: Highlights: A freestanding, highly flexible nanostructured carbon film is fabricated. Such mechanically robust carbon films can suppress the growth of Li dendrites. The semi-tubular carbon film can also protect Li anodes in ambient environment.